Confirmed E-cigarette or vaping product use associated lung injury (EVALI) with lung biopsy; A case report and literature review. (2020) - Cedano, Jorge; Sah, Anuraag; Cedeno-Mendoza, Ricardo; Fish, Heidi; Remolina, Carlos
Abstract: Background: E-cigarette or vaping has become an increasingly popular alternative to smoking tobacco. In September 2019 multiple cases of confirmed E-cigarette or vaping product use associated lung injury were published. However, there is limited knowledge regarding the pathologic mechanism of this condition. Methods: We performed a systematic literature review in PubMed and EMBASE aiming to obtain additional clinical data on confirmed E-cigarette or vaping product use associated lung injury cases with lung biopsy results. With this information we hope to determine whether this condition is related to a histopathological pattern of acute lung injury instead of lipid deposits. Results: Seven articles were reviewed and a total of 27 cases were included. Imaging findings predominantly showed presence of diffuse bilateral ground glass opacities. A majority of patients had complete resolution of the disease. The most common histopathological pattern was organizing pneumonia present in almost half of the patients. Other frequently occurring patterns included diffuse alveolar damage and acute fibrinous pneumonitis; lipoid pneumonia was found in one case. Conclusion: The underlying pathophysiological mechanism in E-cigarette or vaping product use associated lung injury is most likely acute lung injury related to direct inhalant-mediated parenchymal inflammation. Highlights: Majority of cases with confirmed EVALI had diffuse bilateral ground glass opacities pattern. Diffuse ground glass opacities are more associated with typical patterns (organizing pneumonia and diffuse alveolar damage). Histological patterns are more consistent with acute lung injury than lipids deposition. Damage to the lung parenchyma appears to be more related to direct inhaled toxin and/or thermal injury. Variation of the pathologic findings could be secondary to the different types of possible noxious agents.